2019
DOI: 10.1097/scs.0000000000005610
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Skull Dimensions and the Golden Ratio (Φ)

Abstract: The Golden Ratio (Phi, or Φ = 1.618…) is a potentially unifying quantity of structure and function in nature, as best observed in phyllotactic patterns in plants. For centuries, Φ has been identified in human anatomy, and in recent decades, Φ has been identified in human physiology as well. The anatomy and evolution of the human skull have been the focus of intense study. Evolving over millenia, the human skull embodies an elegant harmonization of structure and function. The authors explored the dimensions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The Golden Ratio (Phi, or Φ 1.618...) is a potentially unifying quantity of structure and function in nature, as best observed in phyllotactic patterns in plants. For centuries, Phi (Φ) has been identified in human anatomy, and in recent decades, Φ has been proved in human physiology as well with scientific studies of some authors [9,10]. With the use of Golden Ratio [11] and Fibonacci sequence [12] applied to ultrasonography and mammography, we have experimented and developed a diagnostic map with characteristics of high probability of identifying suspicious lesions at an early stage.…”
Section: Resultsmentioning
confidence: 99%
“…The Golden Ratio (Phi, or Φ 1.618...) is a potentially unifying quantity of structure and function in nature, as best observed in phyllotactic patterns in plants. For centuries, Phi (Φ) has been identified in human anatomy, and in recent decades, Φ has been proved in human physiology as well with scientific studies of some authors [9,10]. With the use of Golden Ratio [11] and Fibonacci sequence [12] applied to ultrasonography and mammography, we have experimented and developed a diagnostic map with characteristics of high probability of identifying suspicious lesions at an early stage.…”
Section: Resultsmentioning
confidence: 99%
“…Over centuries, evidence of its presence in a wide variety of mathematical, biological, and natural systems has been recorded, derived from the idea that it represents the perfect beauty. 17 It has also appeared throughout history in many artistic masterpieces and architectural creations such as Da Vinci’s paintings and the Parthenon, and it is, in brief, an attempt to mathematically and geometrically interpret the captivating mystery of beauty. 18 , 19 Undeterred by its subjective nature, 20 we applied this number in our way: to identify the proper points for injection.…”
Section: Methodsmentioning
confidence: 99%
“…A recent discovery is that φ occurs in the dimensions of the human skull. The work of Tamargo and Pindrik [48] took CAT scanned images of human skulls and considered three points; the nasion (where the frontal bone meets the nasal bones), the inion (a protuberance at the back of the skull) and the bregma (a point at the top of the skull where the frontal and parietal lobes meet). Taking the arc joining the nasion and inion, and dividing it into two sections separated by the bregma, Tamargo and Pindrik found that the resulting sections are Golden, i.e., the bregma makes a Golden cut to this arc.…”
Section: The Brainmentioning
confidence: 99%